Salmeterol tachyphylaxis in steroid treated asthmatic subjects. Issue 11 (November 1996) - Booth, H; Bish, R; Walters, J; Whitehead, F; Walters, E H
Abstract : BACKGROUND: Tachyphylaxis to the protection afforded by salmeterol to broncho-constrictor stimuli after regular use has been described in patients with mild asthma not receiving inhaled corticosteroids. The present study was performed to investigate whether airway tachyphylaxis occurs in symptomatic asthmatic subjects receiving inhaled corticosteroids, the group for whom salmeterol is recommended in clinical practice. METHODS: Thirty one adult patients with symptomatic chronic asthma who were receiving inhaled corticosteroids were randomised in a double blind manner and on a 2:1 basis to receive salmeterol 50 micrograms (n = 22) or placebo (n = 9) twice daily. Baseline forced expiratory volume in one second (FEV1) was measured during the run-in period, on day 0, and after four and eight weeks of regular treatment (following a 36 hour test drug washout period). Airway responsiveness to methacholine was measured one hour after administration of the test drug on these occasions. Diary cards were kept throughout the study and for a two week follow up period. RESULTS: Baseline FEV1 was not significantly different between the treatment groups or between visits. There was significant bronchodilatation one hour after salmeterol administration at 0, four, and eight weeks. No significant tachyphylaxis of the bronchodilator action of salmeterol was seen. Protection against methacholine induced bronchoconstriction reduced from 3.3 doubling dilutions after the first dose of salmeterol to two doubling dilutions after four and eight weeks of regular treatment. Symptom scores and "rescue" salbutamol use were significantly reduced during salmeterol treatment and daytime improvements were maintained into the follow up period. CONCLUSIONS: Inhaled corticosteroids did not prevent tachyphylaxis to the protection afforded by salmeterol to methacholine induced bronchoconstriction. The clinical significance, if any, of these findings remains to be defined.